2005
DOI: 10.1016/j.athoracsur.2005.01.048
|View full text |Cite
|
Sign up to set email alerts
|

Radiation Therapy Potentiates Effective Oncolytic Viral Therapy in the Treatment of Lung Cancer

Abstract: Background-Replication-competent oncolytic herpes simplex viruses (HSV) with deletion of the γ 1 34.5 gene preferentially replicate in and kill malignant cells. γ 1 34.5 codes for ICP 34.5, a protein that enhances viral replication, and is homologous to Growth Arrest and DNA damage Protein 34 (GADD34), a radiation-inducible DNA repair gene. We hypothesized that radiation therapy may potentiate efficacy of oncolytic viral therapy by up-regulating GADD 34 and promoting viral replication.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(37 citation statements)
references
References 23 publications
0
36
0
1
Order By: Relevance
“…We and others have previously shown that IR increased oncolytic HSV-1 replication. [11][12][13][14][15][16][17][18][19][20][21][22][23] The hypothesis tested in this series of experiments was that if varying the timing of IR in relation to the timing of viral injection would result in a further enhancement of viral replication.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We and others have previously shown that IR increased oncolytic HSV-1 replication. [11][12][13][14][15][16][17][18][19][20][21][22][23] The hypothesis tested in this series of experiments was that if varying the timing of IR in relation to the timing of viral injection would result in a further enhancement of viral replication.…”
Section: Discussionmentioning
confidence: 99%
“…[11][12][13][14][15][16][17][18][19][20][21][22][23] Specifically, g 1 34.5 deleted HSV-1 combined with IR resulted in increased viral replication and glioma-xenograft regression in hindlimb and orthotopic preclinical murine glioma models. 11,17 Mechanistic studies have elucidated multiple pathways through which IR enhances viral replication.…”
Section: Introductionmentioning
confidence: 99%
“…15,16 Recent researches to improve the clinical outcome in such patients include altered irradiation fraction schedule and the introduction of chemotherapy, biotherapy, immunotherapy, virotherapy, or gene therapy on a concurrent or adjuvant basis. [17][18][19][20][21][22] Survivin gene expression has been identified in a majority of NSCLC. 3 Additionally, Tamm et al 23 reported that among all the human tumor cells screened, lung cancer cells expressed the highest levels of survivin.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, upregulation of GADD34 expression complements and substitutes for 34.5 gene, leading to increased viral protein synthesis and viral replication [61]. The upregulation of GADD34 expression by radiation in tumor cell infected with HSV was seen in head-and-neck cancer, cholangiocarcinoma and lung cancer [62][63][64]. It is also reported that enhanced expression of host cellular ribonucleotide reductase (RR) following radiation treatment also increased viral replication and tumor cell killing [65,66].…”
Section: Hsv Combined With Conventional Therapiesmentioning
confidence: 91%